2011
DOI: 10.1101/gad.1998111
|View full text |Cite
|
Sign up to set email alerts
|

Zeppo1 is a novel metastasis promoter that repressesE-cadherinexpression and regulates p120-catenin isoform expression and localization

Abstract: Amplification of 8p11-12 in human breast cancers is associated with increased proliferation and tumor grade and reduced metastasis-free patient survival. We identified Zeppo1 (zinc finger elbow-related proline domain protein 1) (FLJ14299/ZNF703) within this amplicon as a regulator of cell adhesion, migration, and proliferation in mammary epithelial cells. Overexpression of Zeppo1 reduces cell-cell adhesion and stimulates migration and proliferation. Knockdown of Zeppo1 induces adhesion and lumen formation. Zep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 65 publications
7
105
0
Order By: Relevance
“…TGF-b was also shown to induce invadopodia formation in EpH4 and MCF10A mammary epithelial cells through up-regulation of Twist1 (Eckert et al 2011) and the focal adhesion protein Hic-5 (Pignatelli et al 2012) to promote matrix degradation and invasion. Furthermore, Zeppo1, a novel metastasis promoter that can repress E-cadherin expression, was found to induce EpH4.9 cells to form invadopodia-like structures in three dimensions (Slorach et al 2011). Together, these studies suggest that the EMT program not only allows carcinoma cells to dissociate from each other but also provides them the ability to degrade ECM for single-cell invasion to initiate the metastatic cascade (Fig.…”
Section: Degradation Of the Ecmmentioning
confidence: 75%
“…TGF-b was also shown to induce invadopodia formation in EpH4 and MCF10A mammary epithelial cells through up-regulation of Twist1 (Eckert et al 2011) and the focal adhesion protein Hic-5 (Pignatelli et al 2012) to promote matrix degradation and invasion. Furthermore, Zeppo1, a novel metastasis promoter that can repress E-cadherin expression, was found to induce EpH4.9 cells to form invadopodia-like structures in three dimensions (Slorach et al 2011). Together, these studies suggest that the EMT program not only allows carcinoma cells to dissociate from each other but also provides them the ability to degrade ECM for single-cell invasion to initiate the metastatic cascade (Fig.…”
Section: Degradation Of the Ecmmentioning
confidence: 75%
“…Several authors have reported that the cell proliferation was promoted in a p120 siRNA stable-transfected NIH3T3 cell line (Wildenberg et al, 2006), in the keratinocytes of p120 conditional-knockout mouse (PerezMoreno et al, 2006;Perez-Moreno et al, 2008) by activation of RhoA signaling. Such an effect of p120 might be reversely linked to E-cadherin or isoform 1A of p120 at the cell membrane (Slorach et al, 2011;Soto et al, 2008). However, others have demonstrated that the growth of MDA-MB-231 cells was promoted by p120 (Soto et al, 2008) or the growth of single MDCK cells was inhibited by p120 knockdown (Dohn et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Another study found that Ki67 was an important regulator, which played an important role in promoting tumor growth, angiogenesis and invasion (Nakamura et al, 2008). FasL plays an important role in the synergistic effect of tumor immunity (Slorach et al, 2011). A previous study found that various natural killer cells prompted loss of FasL in deprived tumor cells, which suggested that it played a role in inhibiting tumorigenesis (Sobin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%